ROLE OF COMMERCIAL BANKS IN INNOVATIVE DEVELOPMENT OF THE ECONOMY - L.M. Sembiyeva,; A.O. Zhagyparova,; М.К. Makysh, (Academic Journal of Physical and Chemical Sciences, 2019)
The article defines the role and importance of the effective functioning of the banking sector to increase the level of innovation and investment development of the country. The necessity of improving the conditions and parameters of the banking and real sectors to stimulate the innovation and investment development of the Republic of Kazakhstan is substantiated. In writing the article, general scientific and special methods were used, such as: system analysis method; content analysis method; comparative analysis method; method of analysis and synthesis; method of systematic approach. The authors analyzed the development of non-primary sectors of the economy in the framework of direct lending, lending to small and medium-sized businesses.